Relationship of mother's knowledge about exclusive breastfeeding: A literature review - Wihyawari, Hermensina; Gurning, Maylar; Mannopposem, Inggerid A (Science Center Group, 2025)
Background: Exclusive breastfeeding provides optimal nutrition for infants during the first six months of life and contributes to improved maternal and child health outcomes. Maternal knowledge is recognized as a critical determinant influencing breastfeeding practices and infant feeding behaviors across different populations. Objective: This study aimed to examine the relationship between mothers’ knowledge about exclusive breastfeeding and breastfeeding practices through a literature review. Methods: The study employed a quantitative literature review approach that analyzed ten research articles examining maternal knowledge and exclusive breastfeeding practices. Studies were selected based on relevance to the research topic and analyzed to identify patterns in study design, sample characteristics, and key findings related to breastfeeding knowledge and practices. Results: The synthesis of the reviewed studies demonstrated that maternal knowledge plays a significant role in shaping breastfeeding practices. Several studies reported statistically significant associations between maternal knowledge and exclusive breastfeeding behavior. Mothers with higher knowledge levels tended to demonstrate stronger breastfeeding commitment and better adherence to recommended breastfeeding practices. However, breastfeeding outcomes were also influenced by cultural beliefs, family support, maternal parity, and access to health information. Conclusion: Maternal knowledge remains a fundamental determinant of exclusive breastfeeding practices. Strengthening maternal education and breastfeeding support programs is essential to improve breastfeeding outcomes and promote optimal infant nutrition.